Arthroscopic Delivery of Matrix-Induced Autologous Chondrocyte Implant: International Experience and Technique Recommendations - Cortese, Fabrizio (Cartilage, 2012)
OBJECTIVE: To identify consensus recommendations for the arthroscopic delivery of the matrix-induced autologous chondrocyte implant. DESIGN: An invited panel was assembled on November 20 and 21, 2009 as an international advisory board in Zurich, Switzerland, to discuss and identify best practices for the arthroscopic delivery of matrix-induced autologous chondrocyte implantation. RESULTS: Arthroscopic matrix-induced autologous chondrocyte implantation is suitable for patients 18 to 55 years of age who have symptomatic, contained chondral lesions of the knee with normal or corrected alignment and stability. This technical note describes consensus recommendations of the international advisory board for the technique of arthroscopic delivery of the matrix-induced autologous chondrocyte implant. CONCLUSIONS: Matrix-induced autologous chondrocyte implantation can be further improved by arthroscopic delivery that does not require special instrumentation. In principle, arthroscopic versus open procedures of delivery of the matrix-induced autologous chondrocyte implant are less invasive and may potentially result in less postoperative pain, less surgical site morbidity, and faster surgical recovery. Long-term studies are needed to confirm these assumptions as well as the efficacy and safety of this arthroscopic approach.